Influences of non-ionic branches on the properties of the anion exchange membranes based on imidazolium functionalized poly (2, 6-dimethyl-1, 4-phenylene oxide). (5th February 2020) - Wan, Ruiying; Zhang, Dengji; Chen, Shaoshuai; Ye, Niya; Yang, Yunfei; He, Ronghuan
Graphical abstract: Highlights: Modifying of the anion exchange membranes with non-ionic branches. The hydrophilicity of grafted branches affects the morphology of the membranes. Membranes with a low hydration coefficient but a high conductivity are obtained. Improved alkaline stability of the membranes by alkyl ether side chains. Abstract: Different nonionic groups were, respectively, grafted onto the backbone of 1, 2, 4, 5-tetramethylimidazolium functionalized poly(2, 6-dimethyl-1, 4-phenyleneoxide) to fabricate anion exchange membranes (AEMs). The presence of the nonionic branches significantly decreased the water swelling of the AEMs by 145% compared to that of the original imidazolium functionalized PPO (Im-PPO) with a comparable hydration level (λ) of around 20. The membrane possessing side chains of the 2-ethoxyethanamine exhibited a hydroxide conductivity of 64 mS cm −1 at 80 °C, while that Im-PPO only showed a conductivity of 48 mS cm −1 under the same conditions. It is found that the presence of ether-containing side chains facilitated formation of more obvious hydrophilic-hydrophobic nanoscopic domains according to the images of atomic force microscope (AFM), and the results of small angle X-ray scattering (SAXS) of the membranes. As a result, the AEM grafted with 2-ethoxyethanamine or 3-methoxypropylamine exhibited higher tensile stress at break and lower methanol permeability than that the pristine Im-PPO membrane. In addition, the ether-containing branches allowed the AEMs to exhibit high alkaline stability. A conductivity of about 54 and 47 mS cm −1 was retained after immersed this kind of AEMs in 1 M KOH at 60 °C for 300 and 750 h, respectively.